Participatory intention and behavior towards riparian peri-urban forests management; an extended theory of planned behavior application - Maleknia, Rahim; ChamCham, Jyran (Frontiers in Psychology, 2024)
Introduction: Peri-urban forests paly crucial role in quality of life and environment for citizens. To effectively utilize the services provided by these forests, it is essential to establish an integrated forest management system that aims to achieve a balance of all ecosystem services. This can be accomplished through a participatory approach that involves key citizen stakeholders. Mountaineers shape a specific group which have showed high pro-environmental behaviors to protect natural resources. This research aimed to examine the influencing factors on mountaineers' intention to participate and their actual behavior in the management of riparian peri-urban forests in this field using extended theory of planned behavior. Methods: Environmental values and perceived barriers were added to original model as additional components to enhance its explanatory power. A sample size of 416 individuals was surveyed using a questionnaire. Data was analyzed using Smart-PLS.The findings of the analysis revealed that the developed model accounted for 75.2% of the variance in mountaineers' intention and 67.8% of behavior. the results demonstrated that three main components of model including attitudes, subjective norms and perceived behavioral control significantly influenced individuals' intentions to participate in peri-urban forests management. Furthermore, intentions were cleared to have a positive influence on actual behavior in this context. Additionally, environmental values were found to be positively correlated with individuals' intentions but not statistically significant behavior toward participate in urban forest management. Perceived barriers were found to have a negative impact on individuals' intentions toward participate in urban forest management. The perceived barriers and behavior had not statistically significant relationship.The results of study provide valuable insights for the development of effective management strategies to promote mountaineers' participation in riparian PUFs management. The study emphasizes the importance of environmental education and awareness campaigns targeted at mountaineers.